Assessing the utility of an online registry for patients monitoring their own warfarin therapy. Issue 4 (30th October 2015) - McCahon, Deborah; Baker, Jennifer M; Murray, Ellen T; Fitzmaurice, David A
Abstract : Aims: To evaluate the utility of an online self-report registry for patient self-monitoring and self-management (PSM) of warfarin therapy. Methods: A prospective observational study of UK-based patients undertaking PSM and recording their international normalised ratio (INR) data via an online registry. Consenting participants recorded INR test dates, results and warfarin dosages using the online registry for a period of 12 months. Participants reported demographic data, disease characteristics and treatment-related adverse events and provided feedback via a survey. Data accuracy was assessed through comparison of INR results recorded online with results stored on 19 INR testing devices. Percentage time spent within therapeutic time in range (TTR) was also examined. Results: Eighty-seven per cent (39/45) completed the study period. Age ranged from 26 to 83 years, 44% had undertaken PSM for >5 years. Sixty-six per cent (25/38) reported that the registry was easy to navigate and use. Forty-two participants contributed a total of 1669 INR results. Agreement between self-reported INR results and source INR data was high (99%). Mean TTR was 76% (SD 18.58) with 83% having >60% TTR. Conclusions: Findings suggest that an online PSM registry is feasible, accurate and acceptable to patients. These findings require confirmation in a larger cohort of PSM patients. An online self-report registry could provide a valuable resource for gathering real world evidence of clinical effectiveness and safety of these developing models of care.